The Effects of Extensive Reading on Turkish Learners' L2 Reading/Writing Performance and Foreign Language Self-Concept - Yılmaz, Melda; Atay, Derin; ER, MUSTAFA (Asia TEFL, 2020)
This study investigates the impact of extensive reading (ER) program, which integrates extensive reading with in-class follow-up writing activities, on Turkish EFL learners' L2 reading/writing and foreign language self-concept (FLSC). In this research, conducted in a Turkish university, experimental design was used and the experimental group was exposed to ER for six weeks different from the control group. Data was collected by means of L2 reading and writing tests and Foreign Language Self-concept Scale (FLSCS) (Er, 2007) given at the beginning and at the end of the intervention, and by means of focus group interviews carried out with 10 randomly chosen experimental group students. Analyses of the data showed a significant difference between control and experimental groups regarding their L2 reading and writing performance. The difference between the groups' FLSC was found to be insignificant, though within group analyses indicated that ER affected the students' FLSC positively. Qualitative data, interviews, supported the quantitative data and revealed that the project also improved students' motivation and self-confidence as well as various aspects of L2 language ability and fostered their positive self images as EFL learners. The insights gained from the study provide important implications for English language teaching programmes in EFL context.
Keywords: Extensive Reading; Writing; Reading; Foreign Language Self-concept